2013
DOI: 10.1166/jnn.2013.7060
|View full text |Cite
|
Sign up to set email alerts
|

Scalability on Roll-to-Roll Gravure Printed Dielectric Layers for Printed Thin Film Transistors

Abstract: The manufacture of thin film transistors with reliable electrical properties, via full-printing on plastic foils, is a key step for the realization of costless and flexible electronics. To reach this goal, the dielectric layers should be smooth and free from failure while maintaining a high capacitance. In this paper, the parameters, affecting the film quality and capacitance of dielectric layers in a roll-to-roll gravure process, were investigated and some parameters were optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…In their case, a stack of silver/dielectric/silver was produced that was used as a wiring pattern to drive R2R assembled LED arrays. Also Yi et al have studied the R2R gravure printing of silver nanoparticle pastes on PET film at 6 m min −1 and the subsequent overprinting of the resulting conductive structures with a dielectric BaTiO 3 ink, also by R2R gravure printing, but at varying speeds of 4, 6, and 8 m min −1 . Their key focus was on the optimization of the printing parameters for the dielectric ink to result in smooth and defect‐free dielectric layers, and they demonstrated that the aspect ratio of the ink cells in the gravure roll is the dominant factor in this respect.…”
Section: Printed Circuitry and Electric Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their case, a stack of silver/dielectric/silver was produced that was used as a wiring pattern to drive R2R assembled LED arrays. Also Yi et al have studied the R2R gravure printing of silver nanoparticle pastes on PET film at 6 m min −1 and the subsequent overprinting of the resulting conductive structures with a dielectric BaTiO 3 ink, also by R2R gravure printing, but at varying speeds of 4, 6, and 8 m min −1 . Their key focus was on the optimization of the printing parameters for the dielectric ink to result in smooth and defect‐free dielectric layers, and they demonstrated that the aspect ratio of the ink cells in the gravure roll is the dominant factor in this respect.…”
Section: Printed Circuitry and Electric Connectionsmentioning
confidence: 99%
“…Scalability of production processes is another important issue, which was investigated by Yi et al, who optimized a number of R2R gravure printing and drying parameters (web speed, cell geometry, drying temperature) for silver nanoparticle based conductive and BaTiO 3 based dielectric inks. Their primary goal was to optimize layer thicknesses and surface morphology and device yields for the capacitors of 100% were reported . A decisive materials property for the printed semiconductor materials is their charge carrier mobility, whereas the transistor devices themselves are typically characterized by their on/off ratio.…”
Section: Transistors and Logicmentioning
confidence: 99%
“…For direct metal printing, metal nanoparticles such as silver, copper, and gold are commonly used for nanoparticle‐based solutions, which enable solution‐based printing processes. Various printing methods have been developed, including inkjet, roll‐to‐roll gravure, flexography, nanoimprinting, microcontact, and screen‐printing . Among the direct printing techniques, screen‐printing is one of the most versatile methods and it has the advantages of low‐cost processing, large‐area patternability, and eco‐friendly manufacturing procedures.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20] The processing characteristics and demonstrated performance of OFETs suggested that they can be competitive for existing or novel applications requiring large-area coverage, structural flexibility, low-temperature processing, and, especially, low-cost processing. [21][22][23][24][25][26] Most OSCs are processed in low temperature by solution processes such as spin-coating, [27][28][29][30] inkjet printing, 22 31-40 and bar coating. 41 42 This feature can dramatically lower the manufacturing cost in processing compared to those traditional inorganic semiconductors.…”
Section: Organic Field-effect Transistorsmentioning
confidence: 99%